Flat-Topped Lattice and Its Properties in Oceanic Turbulence - Rui Cong; Dajun Liu; Yan Yin; Yaochuan Wang; Haiyang Zhong (Journal of Marine Science and Engineering, 2026)
In this paper, based on a theory given by Gori, we have introduced a flat-topped lattice named a multi-cosine-multi-Gaussian correlated beam (McMGCB); the coherence function of the McMGCB consists of a multi-cosine component and a multi-Gaussian component, and the array composed of flat-topped beamlets can be realized by this McMGCB. Based on the extended Huygens-Fresnel integral, the propagation equation of such McMGCB is derived. The McMGCB with smaller δ will split into a beam array faster. And the number of beamlets is determined by Nx and Ny. The flatness of the beamlets is controlled by F. Moreover, the beamlets of such a McMGCB in stronger oceanic turbulence can overlap and merge into one spot. The characterizations of this flat-topped lattice with its adjustable parameters provide a method to generate a rectangular flat-topped beam array, which may have applications that demand a flat-topped array.

Research on Characteristics of the Hermite–Gaussian Correlated Vortex Beam - Rui Cong; Dajun Liu; Yan Yin; Haiyang Zhong; Yaochuan Wang; Guiqiu Wang (Journal of Marine Science and Engineering, 2025)
In this work, a new beam named the Hermite–Gaussian correlated vortex beam (HGCVB) is introduced. The intensity and coherence of this HGCVB in oceanic turbulence are analyzed. The results show that the HGCVB displays a splitting property during propagation, and the HGCVB can evolve into the array profile with hollow center beamlets. The results display that the evolution of the intensity of the HGCVB is manipulated by the coherence length δ0 and topological charge M. Meanwhile, the array distribution of coherence of the HGCVB in oceanic turbulence can evolve into a one-spot pattern on propagation. The results show that this HGCVB evolves from a Gaussian beam into a beam array composed of beamlets with hollow centers and may have a potential application in oceanic turbulence.